2006
DOI: 10.1088/0952-4746/26/4/n01
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gamma irradiation on the grain yield of NigerianZea maysandArachis hypogaea

Abstract: As a follow-up to our earlier investigation on the effect of gamma radiation on the germination and growth of certain Nigerian agricultural crops, the present study sought to determine the effect of gamma radiation on the grain yield of Zea mays (maize) and Arachis hypogaea (groundnut). The seeds were planted after irradiation without the application of fertiliser. The results show that for maize, grain yield for irradiated samples is increased to levels above the unirradiated yield at doses up to about 250 Gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
1
5
1
Order By: Relevance
“…The effects of gamma irradiation on corn-based food and feed products have been reported by several investigators all around the world [4,11,28,32]. In this study, the results showed that the population of F. moniliforme in treated corn samples decreased significantly with increasing doses of gamma irradiation as compared with control (p < 0.05).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The effects of gamma irradiation on corn-based food and feed products have been reported by several investigators all around the world [4,11,28,32]. In this study, the results showed that the population of F. moniliforme in treated corn samples decreased significantly with increasing doses of gamma irradiation as compared with control (p < 0.05).…”
Section: Discussionsupporting
confidence: 55%
“…Gamma irradiation with the dose of ≥5 kGy followed by storage at normal condition successfully prolonged the shelf life of irradiated corns, intended for human and animal consumptions, up to 7 weeks. recent years, there has been increasing interests in the scientific community for the use of gamma irradiation to improve the quality and to extend the shelf life of food and feed products [4,11,16,28,32,39,42,45]. However, contamination of corn by toxigenic fungi and mycotoxins can occur during storage and at any time until consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports showed that mutagenesis by γ-irradiation enhanced ginsenoside production in P. ginseng at dosage 30 Gy-treatment, and shikonin content in callus cultures of Lithospermum erythrorhizon S. significantly increased at dosage 16 Gy-treatment [19,20]. γ-irradiation in other species also showed a significant effect [21,22]. The use of suspension culture methods resulted in significant responses in plant secondary metabolite production.…”
Section: Introductionmentioning
confidence: 99%
“…Maize grain yield depends on the genetic potential of the genotype used, soil characteristics, field management practices and agro-climatic factors. Yield potential is largely determined by a specific combination of several factors, such as solar radiation, soil type, temperature, plant density, genetic potential of a given genotype, biotic and abiotic constraints [6]. All these different factors are potential causes of chronic food shortages encountered in Africa and, in particular, in the Democratic Republic of Congo (DRC) by the fact that they affect most plants of agronomic and economic interest by decreasing accordingly their values.…”
Section: Introductionmentioning
confidence: 99%